Examining the Effect of Social and Intellectual Value on Organizational Performance Based on the Balanced Evaluation Method and Structural Equations in the Iranian Oil Terminals Company - Bidokhti, Abbas Taleb; Esmailpour, Ali Akbar (International Journal of Economics and Financial Issues, 2017)
This study aimed to examine the effects of social and intellectual value on organizational performance based on the balanced evaluation as well as structural equations in the Iranian Oil Terminals Company in 2015. The research method was practical in terms of objectives and descriptive in terms of data collection. The statistical population consists of all the official and unofficial staffs of Iranian Oil terminals Company in 7 operating districts of Khark terminal, Asaluye terminal, Neka terminal, Tehran, Ahvaz, Boushehr and Mahshahr in 2015 which are approximately 2418 people in general. Among these people, 350 were chosen by Cochran formula for limited societies and single stage cluster sampling method as a sample volume. The method of collecting social capitals data was by the means of the standard questionnaire containing 17 questions and based on the model of Nahapiet and Goushal (1998), intellectual capitals are also consist of 20 questions and based on the research by Bettis (1998) and eventually for the organizational performance the standard questionnaire of Kaplan and Norton has been used which is based on the balanced evaluation method and includes 19 questions. The reliability of this questionnaire for all aspects calculated to be higher than 0.7 by the means of Cronbach’s alpha method which indicates an acceptable range of reliability. (AVE>0.5). The data has been analyzed through the Smart PLS software with structural equations modelling method and the final model has been presented. The proper trend of the conceptual model (fig 1) was calculated based on the acceptable and meaningful values for indicators of path coefficients, factor loadings, the presented variance and index of GOF. The results show that there is a direct and positive relationship with 99% level of confidence, between social value and its aspects (structural, recognition oriented and relationship oriented) as well as intellectual capitals and its aspects (human value, structural and relationship oriented) on organizational performance. On the other hand, the highest amount of effectivity among the factors of social and intellectual value on organizational performance was for relationship oriented factors with the rate of 0.560. Keywords: social value, intellectual value, organizational performance, balanced evaluation card JEL Classifications: E37, E32, C53, C5